Propranolol Therapy for Problematic Infantile Hemangioma. Issue 3 (March 2016) - Ng, Marilyn; Knuth, Candace; Weisbrod, Chris; Murthy, Ananth
Abstract : Background: Infantile hemangioma (IH) is a common, benign tumor occurring in up to 10% of white infants. Propranolol has emerged as a front-line therapy for IH. The retrospective study examined the response of propranolol therapy on hemangioma size. Methods: Twenty-seven children (4 to 20 weeks old) with IH were enrolled into the study of oral propranolol solution 2 mg/kg per day divided 3 times daily for 10 months. Response was assessed by size measurements at pretreatment and posttreatment. Scoring was stratified into no response, plateau, and regression groups. Secondary outcomes measured were drug compliance and complications. Results: Twenty-seven consecutive patients with IH were treated with propranolol, of whom 67% completed a 6-month therapy. No correlation was demonstrated between tumor size and age at therapy initiation or patient ( P = 0.7 and P = 0.7, respectively). A large number of infants responded to therapy (85.2%). Response was first observed sooner in the regression group compared to plateau responders (15.15 ± 8.06 and 20.5 ± 18.42 days, respectively). A significant difference in median pretreatment and posttreatment tumor size was noted (4.50 vs 1.55 cm 2, P = 0.02). Attrition was secondary to drug-induced side effects, no response, and dosing noncompliance. Conclusions: Propranolol is a safe and effective first-line therapy for problematic IHs. Therapy should show significant response by 2 weeks. If no response is observed by 3 weeks, then other treatment should be sought.